(untitled) (REMUNOM, 2026)
Popular Education in Health constitutes a theoretical and practical field developed within Brazilian Public Health, based on the articulation between social movements, community practices, and initiatives of professionals committed to the democratization of health care. Unlike traditional educational approaches based on the vertical transmission of information, PEH proposes the shared construction of knowledge between professionals and the population, valuing popular knowledge, community experiences, and collective processes of reflection on living and health conditions. This study aimed to analyze the political dimension of Popular Education in Health, highlighting its contribution to the production of autonomy and the strengthening of processes of resistance and social participation in the field of Public Health. The discussion shows that PEH is based on principles such as dialogue, problematization of reality, and collective construction of knowledge, inspired by Paulo Freire’s critical pedagogy, historically articulating itself with social struggles, the Brazilian Sanitary Reform, and the consolidation of the Unified Health System (SUS). Within the framework of public policies, the institutionalization of the National Policy for Popular Education in Health has strengthened educational practices committed to social participation, health citizenship, and the defense of the right to health. It is concluded that Popular Education in Health is configured as a political instrument capable of stimulating processes of autonomy, strengthening community ties, and expanding forms of resistance against inequalities that permeate the field of health.